KARATERISTIK FISIK BERBAGAI JENIS PASIR MENURUT WARNANYA DI KOTA KENDARI - One, la; N, Edward; Bahrun, Ratna; Makmur, Muammar (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2023)
There are some various types of sand used for construction materials in Kendari City and its surroundings. Visually, the difference in the type of sand used can be seen from the color. This study aims to provide information to stakeholders: the community, government and the business, in considering the selection of technically feasible types of sand for concrete mixtures in Kendari City. The sand used in this study was mointain sand ex. Nambo: light brown sand, white sand and maroon sand, as well as river sand ex. Pohara. Physical characteristic testing carried out by the recommendation of SK SNI No. S-04-1989-F which includes sieving analysis, fineness modulus, aggregate material passing sieve No. 200, organic content, bulk density, specific gravity, and water absorption. This study shows that the physical characteristics of mointain sand ex. Nambo: white sand, light brown sand, and maroon sand do not meet the specifications in relation to the amount of sand passing sieve No. 200. Physical characteristics of river sand ex. Poharadoes not meet the specifications which relating to 2 (two) parameters: the amount of material that passes the sieve No. 200 and organic content.For the use of the sand as a normal concrete mixture, it is recommended that the sand be washed first.